Frailty in lung transplantation: a narrative review of evaluation, optimization, and outcomes - Kercheval, Jacquelyn B.; Mungo, Alison H.; Smith, Joshua B. (Current Challenges in Thoracic Surgery, 2026)
Background and Objective: Lung transplant (LTx) is a curative option for individuals living with end-stage lung disease but the surgery and recovery are taxing, and careful candidate selection is imperative. Frailty is assessed during candidate selection and is of relevance because it represents a potentially modifiable condition associated with peri- and post-operative outcomes. However, while this has been more widely studied in the geriatric patient population, its role in LTx warrants further exploration. The goal of this narrative review is to summarize how frailty in LTx candidates and recipients modifies outcomes, the various methods for evaluation, and peri-operative considerations for the frail LTx candidate.Methods: A PubMed/MEDLINE and National Institutes of Health (NIH)/National Library of Medicine (NLM) review of relevant literature relating to LTx and frailty from January 2000 to December 2025 was performed. Literature was independently reviewed by authors for relevance.Key Content and Findings: Frailty is prevalent in both individuals living with chronic lung disease and surgical candidates in general, and pre-operative assessment for frailty is strongly recommended. While several tools exist to identify patient frailty, their methods are heterogeneous and a consensus has not yet been reached about which is optimal for LTx candidates. Current evidence suggests an association between frailty and poor waitlist and post-transplant outcomes, and there may be an opportunity to intervene on pre-transplant frailty through pulmonary rehabilitation (PR) and nutritional interventions. For individuals that survive transplant surgery, frailty metrics are likely to improve post-operatively.Conclusions: As evidence expands regarding frailty in transplant, individuals historically considered ineligible for transplant are now seen as potential candidates. Understanding the ideal frailty assessment in LTx candidates is of increasing importance, given that interventions exist to potentially improve pre-transplant frailty, which may expand access to LTx and improve outcomes.